BENCHMARKING RAIL FR EIGHT TRANSPORT IN CENTRAL EUROPE (Perner's Contacts, 2018)
Strategies supporting sustainable development of rail freight transport are well known, widely respected and accurately described in the EC´s White paper from March 2011. Despite continuous investment and constant development, rail freight transport in Central Europe faces a number of significant limiting factors. The research intention of this paper is to analyze available sources of information, to point out shortcoming and to suggest possible improvements. Benchmarking is used as a tool to compare performance levels of rail freight carriers in Central European region. The paper highlights the persistent differences in efficiency of rail freight transport providers operating in Central Europe.
Keywords: benchmarking, rail freight transport, Central Europe